THE EFFECT OF MARKETING MIX AND WEBQUAL ON SITE’S CREDIBILITY - Rachmat Agustian; Ujang Sumarwan; Rita Nurmalina (Widyariset, 2015)
In the practice of e-Commerce, another word for online-based sales activity conducted by firms or organizations via the internet, the credibility of the host site is important. A credible site will be able to attract more visitors, thus increasing the probability of selling the goods or services offered in that particular site. Credibility assessment is not only based on the usability, information quality, and interaction quality of the site alone, but is also based onattributes of marketing mix, which include the originality of the product, the promotion that is currently available, the existence of additional information in the site, as well as other factors. This research aims to link the attributesof marketing mix and site quality assessment (WebQual), such as the usability, information quality, and interaction quality to the credibility of a site. The research models the relation by constructing a structural equation modeling(SEM) and uses two data analyzing techniques: descriptive analysis using cross tabulation and frequency table, and a variance based model analysis using the Partial Least Square (PLS) method. The results show that site credibility assessment on marketing mix improves due to occurring bonus or promotions, selling well known brands, and the availability of delivery services that can be monitored by buyers. In WebQual metrics, site credibility improves due to visitor’s ease of understanding, trust/reliability, and security while visiting or conducting purchases. Site credibility constructions rely on additional vendor information such as contact numbers, vendor ID (address, structure, awards, etc.), shopping guidelines, and feedback speed to customers queries.